Positive effects of renal denervation on markers of cardiovascular inflammation and left ventricular mass. 24-months follow-up - E. S. Sitkova; V. F. Mordovin; S. E. Pekarskiy; T. M. Ripp; T. R. Ryabova; А. Yu. Falkovskaya; V. A. Lichikaki; I. V. Zyubanova; A. Е. Baev; A. M. Gusakova (Кардиоваскулярная терапия и профилактика)
Aim. To study the long-term effect of renal denervation (RDN) on left ventricular mass (LVM) and inflammatory markers in resistant hypertensive patients.Material and methods. Forty-one patients with resistant hypertension and 24-h blood pressure (BP) 158,7±15,8/87,3+14,6 mmHg, aged 56,6+10,2 years, were enrolled in the study and undergone RDN. Mean 24-h BP, left ventricular mass (transthoracic echocardiography), high sensitivity C-reactive protein (hsCRP), interleukin- 1β (IL1β), IL-6, IL-10) and tumor necrosis factor alpha (TNF- α) were assessed at baseline and 2 years after the RDN.Results. A baseline prevalence of left ventricular hypertrophy (LVH) was 90,2%. Two years after RDN LVM and interventricular septum (IVS) decreased significantly (p<0.05 for both). Decrease in myocardial mass (∆LVM >0 g) was documented in 24 patients. The regression of LVM was accompanied by a significant decrease in levels of inflammatory markers — hsCRP by 38,3% (p=0,031), TNF-α by 60,7% (p=0,009), IL- 1β — by 71,1% (p=0,001), and IL-10 by 58,2% (p=0,001). In patients in the absence of LVM regression only TNF-α decreased significantly (-68,8%, p=0,001). There was no correlation between changes of LVM and the inflammatory markers at 24 months after RDN.Conclusion. The RDN in RH patients may have long-term cardioprotective effect in terms of significant regress of LVH, which may be partly attributed to the regress in systemic or myocardial inflammation.